2020
DOI: 10.3390/nu12041200
|View full text |Cite
|
Sign up to set email alerts
|

Food Involvement, Eating Restrictions and Dietary Patterns in Polish Adults: Expected Effects of Their Relationships (LifeStyle Study)

Abstract: Understanding the factors that coexist with healthy and unhealthy eating behaviors is prevalent and important for public health. The aim of this study was to investigate the associations between food involvement, eating restrictions, and dietary patterns in a representative sample of Polish adults. The study was conducted among a group of 1007 adults. Questions with the answers yes or no were used to obtain the data regarding eating restrictions. Data relating to food involvement were obtained with the Food In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 42 publications
4
28
1
Order By: Relevance
“…Staff canteens are crucial because they could offer the intake of healthy, well-balanced food according to modern guidelines [ 11 , 12 ]. This is also related to the development of good eating habits [ 11 , 13 ], which also depend on acceptability, food neophobia, food intake, culture, and gender [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Staff canteens are crucial because they could offer the intake of healthy, well-balanced food according to modern guidelines [ 11 , 12 ]. This is also related to the development of good eating habits [ 11 , 13 ], which also depend on acceptability, food neophobia, food intake, culture, and gender [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to examine associations between a range of dietary and lifestyle behaviors as well as nutrition knowledge among Polish pharmacists. We used a validated, culture-specific, tool with reliable psychometric properties [ 9 – 11 , 13 16 ]. Our results revealed that dietary patterns among this group of health-care professionals are moderate and comparable to the general adult Polish population [ 11 ], with slightly higher values of both, the Pro-Healthy Diet Index (pHDI-10) and the Non-Healthy-Diet-Index (nHDI-14).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to examine associations between a range of dietary and lifestyle behaviors as well as nutrition knowledge among Polish pharmacists. We used a validated, culture-specific, tool with reliable psychometric properties [9][10][11][13][14][15][16]. Our results revealed that dietary patterns among this group of health-care professionals are moderate and comparable to the general adult Polish population [11], with slightly higher values of both, the Pro-Healthy Diet Index (pHDI-10) and the Table 5 The mean values and interquartile ranges (Q25-Q75) of consumption frequencies of the selected food items together with the Pro-Healthy Diet Index (pHDI-10), the Non-Healthy-Diet-Index (nHDI-14) and nutrition knowledge test scores in our sample in comparison with Polish healthy population data [7].…”
Section: Discussionmentioning
confidence: 99%
“…These people are often strategically likely to use vigilance as a means to avoid negative outcomes [57]. In eating behavior, the desire to eating different types of food may activate an individual' eager to obtain the goal [58]. As eating behavior is a national instinct in human, the choice between food alternatives may naturally activate a promotion orientation.…”
Section: The Mediating Role Of Promotion Focusmentioning
confidence: 99%